2009
DOI: 10.1021/jp9038623
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Studies on the Complexation and Spectroscopy of Uranyl Ligated with Acetonitrile and Acetone Derivatives

Abstract: The coordination of nitrile (acetonitrile, propionitrile, and benzonitrile) and carbonyl (formaldehyde, acetaldehyde, and acetone) ligands to the uranyl dication (UO22+) has been examined using density functional theory (DFT) utilizing relativistic effective core potentials (RECPs). Complexes containing up to six ligands have been modeled in the gas phase for all ligands except formaldehyde, for which no minimum could be found. A comparison of relative binding energies indicates that 5-coordinate complexes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 33 publications
5
24
0
Order By: Relevance
“…8 The present work builds upon the previous results by allowing water, as well as nitrile ligands, to bind to uranyl.…”
Section: Ligand Addition Reactionsmentioning
confidence: 64%
See 1 more Smart Citation
“…8 The present work builds upon the previous results by allowing water, as well as nitrile ligands, to bind to uranyl.…”
Section: Ligand Addition Reactionsmentioning
confidence: 64%
“…As noted in previous work, 8 the sixth ligand can be a direct ligand (although weakly bound), or it can add to the first solvent shell. There are three possibilities when two, three, and four nitrile ligands are present.…”
Section: +mentioning
confidence: 78%
“…Our hypothesis was that DMF as the co-solvent, with a gas-phase basicity of 857 kJ/mol, compared to basicities of 660, 748, and 782 kJ/mol, for water, acetonitrile, and Figure S1) acetone, respectively [20] [21], and the high basicity of DMF relative to acetonitrile or acetone should result in greater electron donation to the metal center by the first four ligands, which may render addition of a fifth DMF ligand energetically unfavorable. Similar shifts to higher stability of complexes with four ligands relative to those with five have been observed previously with gas-phase uranyl-nitrile complexes [12].…”
Section: Resultsmentioning
confidence: 99%
“…Kaltsoyannis et al, however, did not find any evidence of the "p competition", confirming only in part the claims by Clark et al 3 Windus et al studied the uranyl(VI)-acetonitrile bonding interaction and found that the ligand p donation to the U 5f orbital lead to the weakening of the U-O yl bond. 7 Denning and coauthors 8-9 made an extensive series of spectroscopic and theoretical investigations on the electronic structures of UO 2 Cl 4 2and Cs 2 UO 2 Cl 4 . They discussed the equatorial ligand interaction with the uranyl molecular orbitals (MOs) in these complexes.…”
Section: Introductionmentioning
confidence: 99%